2014
DOI: 10.1073/pnas.1309723111
|View full text |Cite
|
Sign up to set email alerts
|

Principles of scientific research team formation and evolution

Abstract: Research teams are the fundamental social unit of science, and yet there is currently no model that describes their basic property: size. In most fields teams have grown significantly in recent decades. We show that this is partly due to the change in the character of team-size distribution. We explain these changes with a comprehensive yet straightforward model of how teams of different sizes emerge and grow. This model accurately reproduces the evolution of empirical team-size distribution over the period of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
144
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(152 citation statements)
references
References 33 publications
(49 reference statements)
3
144
0
5
Order By: Relevance
“…While this trend began decades ago (Price, 1963;Swatez, 1966), the sizes of contemporary research teams in many fields are beginning to approach that of medium-sized firms (Biagioli, 2003;Birnholtz, 2006;Milojević, 2014;Pavlidis et al, 2014;Salonius, 2008). Rather than a focus on an individual's lab bench, scientific work increasingly takes place in a setting that more closely resembles a small "factory" or "quasi-firm", run by a "small businessperson" lab director (Etzkowitz, 1983;Hackett, 1990;Latour and Woolgar, 1979;Shrum et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While this trend began decades ago (Price, 1963;Swatez, 1966), the sizes of contemporary research teams in many fields are beginning to approach that of medium-sized firms (Biagioli, 2003;Birnholtz, 2006;Milojević, 2014;Pavlidis et al, 2014;Salonius, 2008). Rather than a focus on an individual's lab bench, scientific work increasingly takes place in a setting that more closely resembles a small "factory" or "quasi-firm", run by a "small businessperson" lab director (Etzkowitz, 1983;Hackett, 1990;Latour and Woolgar, 1979;Shrum et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The need for diverse research approaches and transdisciplinary teams to address complex problems is increasingly recognized (39). However, a greater emphasis on "team science" will require a radical reconsideration of how scientists are organized, supported, and rewarded (40)(41)(42).…”
mentioning
confidence: 99%
“…However, it also has a so-called hook for the authors with small number of collaborators, a feature identified by Wagner and Leydesdorff (2005) and further studied in Milojević (2010). This feature is important and the recent model of scientific research team formation and evolution (Milojević, 2014) has identified the likely underlying reason for its existence. It follows from two modes of knowledge production: one with relatively small core teams following Poisson distribution and another with extended teams which due to preferential attachment can become very large.…”
Section: Collaboration Networkmentioning
confidence: 98%